End of Sustainability : Resilience and the Future of Environmental Governance in the Anthropocene - Benson, Melinda Harm (Environment and society., 2017)
"In this provocative study, Melinda Harm Benson and Robin Kundis Craig argue that sustainability--the long-term ability to continue engaging in a particular activity, process, or use of natural resources with some marginal changes--is no longer a feasible goal as climate change has dramatic impacts on our world. Sustainable development, which considers environmental and natural resources in order to assure their continuing availability, has failed to stop climate change or sufficiently adjust to the demands of a rapidly changing environment. Instead the authors argue for the concept of resilience as a better guide to environmentally sound policies. Unlike sustainability, which seeks to continue what we've done in the past, resilience anticipates the need for dramatic change and focuses on adapting human systems. In light of the possibility of non-linear and sometimes irreversible change, resilience considers the degree to which we need to adjust both our ways of living and our personal and societal objectives"--Provided by publisher